Homotopy Perturbation Transform Algorithm for Solving (2+1) Dimensional Type of the Zakharov–Kuznetsov Equations - Lawal, O.W.; Jagun, O.Z.; Erinle-Ibrahim, L.M. (Kathmandu University Journal of Science, Engineering and Technology, 2021)
In this research, homotopy perturbation transform method (HPTM) is used to present the approximate analytical solutions of (2+1) dimensional type of the Zakharov–Kuznetsov nonlinear partial differential equations. This method gives solutions without any linearization and discretization or restrictive assumptions. Special cases of and are chosen as examples to show the capability and efficiency of the method. Maple 19.0 software is employed to compute the series generated from the algorithm. The results show that HPTM is very simple, reliable and effective in solving nonlinear problems.